(untitled) (Contemporary Education and Teaching Research, 2023)
The arrival of the big data era is profoundly changing people’s social structure and working methods, and the field of education is naturally not spared. Driven by a large amount of information and technology, the pace of educational change is becoming more and more rapid, and networking and intelligence have become the keywords of the new generation of education, especially in the aspect of network ideological and political education in colleges and universities, this change is more important. This paper will explore these new trends and challenges in depth, analyze their impact and significance on network ideological and political education in colleges and universities, and combine them with specific teaching cases to put forward corresponding solution strategies and directions, aiming to further promote the modernization of the cause of ideological and political education in China’s colleges and universities.